EFFECT OF BRAND IDENTITY AND LIFESTYLE ON PURCHASING DECISIONS WITH EXPERIENTIAL BUYING AS MODERATING IN BABY BOOMERS IN MEDAN CITY RESTAURANTS - Haidiani Putri, Yessi; Karina Fawzeea Sembiring, Beby; Absah, Yeni (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Many businesspeople have benefited financially from this culinary industry. However, many people in the culinary industry have failed financially due of poor marketing tactics and subpar customer service. It implies that a culinary company's ability to outperform the competition depends on the adoption of an effective marketing plan and strong consumer interactions. The purpose of this study is to ascertain how brand identity and lifestyle affect purchasing decisions that are tempered by experience shopping. Slovin sampling was used to perform this study on all restaurant patrons in Medan City. Modified regression analysis is used for the analysis. Purchase decisions are unaffected by brand identity. Purchase decisions are impacted by a person's lifestyle. The impact of brand identity on purchase decisions might be tempered through experiential buying. Experiential purchasing is unable to mitigate the impact of lifestyle on purchasing choices. At eateries in Medan City, Babyboomers' purchase decisions are influenced by both brand identity and lifestyle. At eateries in Medan City, experiential buying can reduce the simultaneous effect of brand identity and lifestyle on baby boomers' purchase decisions